Accidentes laborales, enfermedades profesionales y uso de elementos de protección personal en veterinarios de pequeños animales - Gómez de la Torre, N. (2015)
A cross-sectional study was performed in N=23 small animal practitioners in the city of Mendoza, Argentina, by means of personal interviews using a structured questionnaire. Statistical analysis included Fisher?s exact test and Student?s t test. As much as 30.4% did not have any medical coverage and 47.8% had suffered some zoonotic disease, mainly external parasites. All were injured in labore (mainly needlesticks, bites and scratches). Gloves were the most used protective element in labore, but the frequency of use of other elements was low. Only 23.1% of those working in radiology (n=13) were licensed, 38.5% were registered by the health service and none used a dosimeter. Young and female veterinarians adopted protective practices more frequently than experienced and male veterinarians.